Predicting moral attitudes and antisocial behavior in young team sport athletes: A self‐determination theory perspective. Issue 4 (26th February 2019) - Mallia, Luca; Lucidi, Fabio; Zelli, Arnaldo; Chirico, Andrea; Hagger, Martin S.
Abstract: Identifying the factors associated with prosocial and antisocial behaviors in youth sport may provide evidence to inform interventions aimed at promoting prosocial behaviors and minimizing rule transgressions in young athletes. We investigated relations among social‐contextual factors (e.g., social support), personal motivational factors (e.g., psychological need satisfaction and motivation), young athletes' attitudes toward prosocial (e.g., keeping winning in proportion) and antisocial (e.g., acceptance of cheating and gamesmanship) behaviors, and their actual rule violations during matches in two samples of athletes. Participants in Sample 1 were young team sport athletes ( N  = 355) and participants in Sample 2 were young male futsal players ( N  = 296). Athletes in Sample 1 completed validated self‐report measures of perceived autonomy support, basic need satisfaction, and autonomous and controlled motivation from self‐determination theory, moral attitudes, and past cheating behaviors. Athletes in Sample 2 completed identical measures and two additional behavioral measures: athletes' self‐reported number of yellow cards received during competition in the last 6 months and the number of yellow cards athletes received from referees in the subsequent 2 months from competition records. We found significant relations between psychological need satisfaction and self‐determined motivation, and athletes' moral attitudes in both samples. These effects held when statistically controlling for past behavior. Importantly, our prospective analysis of Sample 2 indicated that attitudes toward antisocial behaviors predicted athletes' rule violations during subsequent tournament matches. Findings indicate that promoting autonomous motivation and need satisfaction through autonomy support may foster attitudes toward prosocial behaviors, and minimize rule transgressions, in young athletes.